Altered muscle coordination when pedaling with independent cranks - Hug, François; Boumier, Florian; Dorel, Sylvain (Frontiers in Physiology, 2013)
Pedalling with independent cranks ensures each leg cycles independently of the other, and thus eliminates the contribution of the contralateral leg during the upstroke phase. Consequently the subject is required to actively pull-up the pedal to complete the cycle. The present study aimed to determine the acute effect of the use of independent cranks on muscle coordination during a submaximal pedalling exercise. Ten healthy males were asked to perform submaximal pedaling exercises at 100 Watts with normal fixed cranks (control condition) or independent cranks. Both 2-D pedal forces and electromyographic (EMG) patterns of 10 lower limb muscles were recorded. When the mean EMG activity across the cycle was considered, the use of independent cranks significantly increased the activity level compared to control for Tibialis anterior (P=0.0017; +336±302%), Gastrocnemius medialis (P=0.0005; +47±25%), Rectus femoris (P=0.005; +123±153%), Biceps femoris – long head (P=0.0001; +162±97%), Semimembranosus (P=0.0001; +304±192%), and Tensor fascia latae (P=0.0001; +586±262%). The analysis of the four pedalling sectors revealed that the increased activity of hip and knee flexors mainly occurred during the top dead center and the upstroke phase. In addition, a high inter-individual variability was found in the way the participants adapted to pedalling with independent cranks. The present results showed that the enforced pull-up action required when using independent cranks was achieved by increasing the activation of hip and knee flexors. Further studies are needed to determine whether training with independent cranks has the potential to induce long-term changes in muscle coordination, and, if so, whether these changes are beneficial for cycling performance.